Comments on 'Analysis and Design of Three-Layer Perfect Metamaterial-Inspired Absorber Based on Double Split-Serration-Rings Structure' - Srivastava S.K.; Meshram M.K. (My University, 2025)
This comment provides a critical analysis of a recent paper by Si-Jia-Li et al. In this article, a linear reflective polarization converter was mistakenly identified as a metamaterial-inspired wideband and multiband absorber for two different rotatory angles of serration rings. We have demonstrated that there exhibits substantial orthogonal polarization reflection from reported structure for an incident electromagnetic wave. A careful analysis of the proposed structure reveals that by including the cross-polarized reflected component of the incident wave in the estimation of absorptivity, the absorptivity level drastically decreased from 90% to below 30% over most of the claimed frequency range. Moreover, the reported structure produces more than 90% polarization conversion efficiency rather than high absorptivity performance over the claim operating band. © 1963-2012 IEEE.